2020
DOI: 10.1175/mwr-d-19-0327.1
|View full text |Cite
|
Sign up to set email alerts
|

The Lightning Distribution of Tropical Cyclones over the Western North Pacific

Abstract: This study examines the characteristics of tropical cyclone (TC) lightning distribution and its relationship with TC intensity and environmental vertical wind shear (VWS) over the western North Pacific. It uses data from the World Wide Lightning Location Network and operational global analysis data from National Centers for Environmental Prediction Final Analysis for 230 TCs during 2005–2017. The spatial distribution of TC lightning frequency and normalized lightning rate demonstrates that the VWS dominates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…WWLLN reports that "recent research indicates our detection efficiency for strokes about 30 kA is approximately 30% globally". More recently, [59] stressed the fact that in the early stages of the network (before 2008), the detection efficiency was low because there were only a relatively small number of sensors. Lightning efficiency has been monotonically increasing since the early days of the network [58], by a factor of about 1.25 (60 in 2012, [58]; to over 70 in recent years, http://wwlln.net/ accessed on 28 Decmber 2021).…”
Section: Data and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…WWLLN reports that "recent research indicates our detection efficiency for strokes about 30 kA is approximately 30% globally". More recently, [59] stressed the fact that in the early stages of the network (before 2008), the detection efficiency was low because there were only a relatively small number of sensors. Lightning efficiency has been monotonically increasing since the early days of the network [58], by a factor of about 1.25 (60 in 2012, [58]; to over 70 in recent years, http://wwlln.net/ accessed on 28 Decmber 2021).…”
Section: Data and Proceduresmentioning
confidence: 99%
“…Lightning efficiency has been monotonically increasing since the early days of the network [58], by a factor of about 1.25 (60 in 2012, [58]; to over 70 in recent years, http://wwlln.net/ accessed on 28 Decmber 2021). Studies have also used some sort of adjustment factors for WWLLN D based on the LIS/OTD (Lightning Imaging Sensor, LIS, and Optical Transient Detector, OTD) climatology [59], although LIS/OTD has a quite different detector sensor detecting pulses of illumination (produced by lightning) above background levels. Estimates of precipitation have been possible due to satellite monitoring programs such as the Tropical Rainfall Measuring Mission (TRMM, https://gpm.nasa.gov/missions/ trmm, accessed on 28 December 2021), the Global Precipitation Measurement (GPM) mission https://gpm.nasa.gov/missions/GPM, accessed on 28 December 2021), and CHIRPS (https://www.chc.ucsb.edu/data/chirps, accessed on 28 December 2021), a project using rain gauge and satellite observations.…”
Section: Data and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Price et al [13] found that in the majority of tropical cyclones, lightning frequency and maximum sustained winds are significantly correlated (mean correlation coefficient of 0.82); however, the maximum sustained winds and minimum pressures in hurricanes are preceded by increases in lightning activity approximately one day before the peak winds. Numerous other recent studies have also investigated the link between lightning and tropical cyclones [14][15][16][17]. In this study, we expand on these previous studies to investigate the role of tropical cyclones on the transport of water vapor into the upper troposphere.…”
Section: Introductionmentioning
confidence: 94%
“…O V shear pode ser calculado de duas maneiras: (i) considerando a diferença da intensidade do vento entre dois níveis de pressão e, (ii) considerando a diferença vetorial como mostrado na Equação 4. Essa última é chamada, no inglês, de Environmental Vertical Wind Shear (Lin & Chou, 2020). No cálculo do IPG é usada a maneira (ii), mas para a rápida visualização e compreensão dos resultados, a maneira (i) é mais apropriada, pois quando o cisalhamento mostra valores positivos (negativos) indica que os ventos em altos níveis são mais intensos (fracos) do que em baixos níveis da atmosfera.…”
Section: Cisalhamento Vertical Do Vento Horizontal (V Shear ) (200 Hpunclassified